Factores que determinan la morosidad en los clientes de Servicios Empresariales y Financieros SEF Perú Holding SAC Iquitos 2023 - Gonzales Tamani, Jorge Luis (2025)
The objective of this final report was to identify the factors that determine delinquency among clients of Services Empresariales y Financiers SEF Perú Holding SAC Iquitos 2023. Applied research was used, explanatory level, with a non-experimental design, consisting of a sample of 87 clients from whom a questionnaire was used to collect information. The results revealed, regarding the cultural factor, that clients have internalized ethical values related to financial compliance and demonstrate economic responsibility. Their financial knowledge is limited and they have little access to information or training on this topic. Furthermore, the practice of saving is not fully established, which indicates the need to strengthen financial education and promote sustainable habits to improve economic stability. Regarding delinquency, clients display good payment behavior, although they sometimes have difficulty meeting deadlines. They are not considered high risk, but there are limitations in their payment capacity and in developing a solid credit history. Furthermore, late payment notifications are rare, suggesting opportunities to improve preventive management and customer follow-up.